Allergen‐specific immunotherapy induces the suppressive secretoglobin 1A1 in cells of the lower airways. Issue 8 (6th March 2021) - Zissler, Ulrich M.; Jakwerth, Constanze A.; Guerth, Ferdinand; Lewitan, Larissa; Rothkirch, Sandra; Davidovic, Miodrag; Ulrich, Moritz; Oelsner, Madlen; Garn, Holger; Schmidt‐Weber, Carsten B.; Chaker, Adam M.
Abstract: Background: While several systemic immunomodulatory effects of allergen‐specific immunotherapy (AIT) have been discovered, local anti‐inflammatory mechanisms in the respiratory tract are largely unknown. We sought to elucidate local and epithelial mechanisms underlying allergen‐specific immunotherapy in a genome‐wide approach. Methods: We induced sputum in hay fever patients and healthy controls during the pollen peak season and stratified patients by effective allergen immunotherapy or as untreated. Sputum was directly processed after induction and subjected to whole transcriptome RNA microarray analysis. Nasal secretions were analyzed for Secretoglobin1A1 (SCGB1A1) and IL‐24 protein levels in an additional validation cohort at three defined time points during the 3‐year course of AIT. Subsequently, RNA was extracted and subjected to an array‐based whole transcriptome analysis. Results: Allergen‐specific immunotherapy inhibited pro‐inflammatory CXCL8, IL24, and CCL26 mRNA expression, while SCGB1A1, IL7, CCL5, CCL23, and WNT5B mRNAs were induced independently of the asthma status and allergen season. In our validation cohort, local increase of SCGB1A1 occurred concomitantly with the reduction of local IL‐24 in upper airways during the course of AIT. Additionally, SCGB1A1 was identified as a suppressor of epithelial gene expression. Conclusions: Allergen‐specific immunotherapy induces a yet unknown local gene expression footprint in the lower airways that on one hand appears to be a result of multiple regulatory pathways and on the other hand reveals SCGB1A1 as novel anti‐inflammatory mediator of long‐term allergen‐specific therapeutic intervention in the local environment. Abstract : Allergen‐specific immunotherapy inhibited pro‐inflammatory CXCL8, IL24 and CCL26 mRNA expression in alveolar sputum cells. SCGB1A1 was induced in lower airway cells independently of the asthma status and allergen season. The epithelial type‐2 (E2) cytokine IL‐24 was reduced following 3 years of AIT‐treatment, while SCGB1A1 was significantly increased and identified as a suppressor of epithelial gene expression.